The millipede family Striariidae Bollman, 1893. VII. Petra sierwaldae, n. gen., n. sp., a minute millipede from Idaho, USA (Diplopoda, Chordeumatida, Striariidae) - Shear, William A.; Marek, Paul E.; Bond, Jason E.; Wesener, Thomas (Zootaxa, 2022)
Petra sierwaldae, n. gen., n. sp. is described from males and females collected at four localities in Kootenai County, Idaho, USA. The new genus is defined by its unique gonopod and ninth leg anatomy, a notched collum and single ommatidium on each side of the head, and lacking third coxal flasks as well as having modified fifth coxae.